Interference Analysis of Weather Radar at The Meteorological Station - mahmudi, muhamad nur; Anhar, Anhar; Panjaitan, Hatopan; Rosadi, Feby (International Journal of Electrical, Energy and Power System Engineering, 2024)
This research aims to analyze the disturbances that occur at the Sultan Syarif Kasim II Meteorological Station Weather Radar and provide appropriate treatment to stop the source of the disturbance. For this reason, the following steps are arranged: Literature studies, preparation for mitigating interference, measurement, interference analysis, and interference resolution. After applying measurements, the following results were obtained: The interference location point is on the azimuth line (8.07° and 37.84°), Noise floor level -107.3 dBm at a frequency of 6500 MHz when SSID PermanaNET#02 5825 MHz is on, noise floor level -111.1 dBm at a frequency of 6500 MHz when SSID PermanaNET#02 5825 MHz is off, distance between BMKG Radar station to Point of Presence (PoP) ISP PT. Medianusa Permana is very close ±200 meters, antenna SSID PermanaNET#02 5825 MHz pointing to the BMKG Radar Station, and sensitivity of the EEC DWSR–2500C Radar Device is -113 dBm. Interference at the 6500 MHz radar frequency comes from the Out Of Band Emission frequency 5825 MHz (SSID PermanaNET#02). Following this, the interference is mitigated by the off-air method, which is deactivation of the PermanaNET SSID#02 device.